2014
DOI: 10.1152/ajprenal.00532.2013
|View full text |Cite
|
Sign up to set email alerts
|

Human podocytes perform polarized, caveolae-dependent albumin endocytosis

Abstract: The renal glomerulus forms a selective filtration barrier that allows the passage of water, ions, and small solutes into the urinary space while restricting the passage of cells and macromolecules. The three layers of the glomerular filtration barrier include the vascular endothelium, glomerular basement membrane (GBM), and podocyte epithelium. Podocytes are capable of internalizing albumin and are hypothesized to clear proteins that traverse the GBM. The present study followed the fate of FITC-labeled albumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
88
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 47 publications
5
88
0
2
Order By: Relevance
“…6 We hypothesized that an increased flow of albumin across the filtration barrier may force the podocytes to clear the basement membrane and/or the subpodocyte space (SP) of accumulating albumin. In line with our hypothesis, cultured immortalized human podocytes were shown to perform caveolae-dependent endocytosis of albumin, 7 and albumin-containing vesicles could be observed by electron microscopy in mouse, rat, and human tissue. 8 Using intravital multiphoton microscopy (MPM) and electron microscopy, we found that Ang II infusion promotes the endocytosis of albumin by podocytes.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…6 We hypothesized that an increased flow of albumin across the filtration barrier may force the podocytes to clear the basement membrane and/or the subpodocyte space (SP) of accumulating albumin. In line with our hypothesis, cultured immortalized human podocytes were shown to perform caveolae-dependent endocytosis of albumin, 7 and albumin-containing vesicles could be observed by electron microscopy in mouse, rat, and human tissue. 8 Using intravital multiphoton microscopy (MPM) and electron microscopy, we found that Ang II infusion promotes the endocytosis of albumin by podocytes.…”
supporting
confidence: 84%
“…7 Our immunostainings confirmed the expression of caveolin-1 in the podocytes ( Figure 4A) of the Munich Wistar Froemter (MWF) rat and revealed that glomerular albumin colocalized with caveolin-1 ( Figure 4B). Because megalin colocalizes with caveolae in various cell types 10 and because the proximal tubular uptake of filtered albumin is mediated by the megalin/cubilin complex, [11][12][13] we hypothesized that megalin may be involved in the uptake of albumin by podocytes.…”
Section: Podocyte Albumin Endocytosis Is Megalin Dependentsupporting
confidence: 63%
See 1 more Smart Citation
“…12 The growing number of studies showed that the SD is involved in the occurrence and transmission of signal transduction which maintained podocyte normal biological function, such as proliferation, differentiation, survival, endocytosis and cytoskeletal composition. [13][14][15] Therefore, SD which acts as a static molecular sieve and the highly dynamic complex, had a key effect on maintaining the normal structure of podocyte and functional integrity of the glomerular filtration barrier. 16 A recent report showed that glomerular mRNA level of CD2AP was significantly decreased in children with minimal change nephritic syndrome and primary IgA nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this work, we sought to determine the functional significance of RalA recruitment and association with FilA and Cav-1 in human lung microvascular endothelial cells (HLMVECs). We observed RalA activation and recruitment to EC caveolae upon stimulation of albumin, perhaps the best studied macromolecular cargo of endothelial caveolae (24), and demonstrated that FilA is not required for RalA activation by albumin, but rather that it is essential for RalA association with caveolae. Furthermore, a significant decrease in caveolae-mediated internalization of albumin was detected in cells treated with RalA siRNA, suggesting that RalA activation is critical for efficient caveolae-mediated transport.…”
mentioning
confidence: 80%